Plan de mejoramiento de la producción porcina, mediante una alimentación alternativa, en la parroquia Cojitambo, cantón Azogues, provincia de Cañar - López González, Ángel Oswaldo (2016)
The research called "Plan Improvement Swine Production by alternative feeding in Cojitambo parish, canton Azogues, Cañar Province", aimed to the execution of a diagnosis of swine situation by SWOT analysis, costing , income and expenses for profitability, selecting breeding strategies address the existing problems in feeding pigs, and develop an improvement plan in pig production by an alternative feed. The methodology used was the application of scientific, analytical, inductive and deductive methods, techniques of direct observation and indirect observation, interviews by questionnaire instrument. The variables studied were the list of pork producers, the situation analysis of pig production, economic analysis (profitability), strategy selection of projects and activities, same as were implemented in an improvement plan for the production and feeding pigs. The results show that the current supply of pigs is rustic, dominated the Creole race, pigs are fed with food waste, management is ancestral, without technique, workmanship is poor, and farmers lack training, by therefore profitability in most farms is low. The average value of each fattening pig with an average weight of 100 kilos is $ 300 why there is great demand for the product, but there are comments from consumers who claim that pork has a different flavor. We conclude that in the field of Cojitambo producers are ready to start an alternative power in raising pigs, in order to obtain a quality product that is healthy, is in good condition for human consumption, and can be marketed in the sector. This improvement plan Parish GAD is recommended to be taken into account and socialece with pork producers in the sector in an effort to provide technical support, improve the quality of the final product, and thus get a better return. Similarly reference to improve the infrastructure of swine facilities is ensuring longer life and also provide better living conditions in what is hygiene, health, taking into account the biosecurity measures and continue raising landrace pigs, applying strategies, projects and activities described in the research paper.